(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the issues related to explaining and teaching the processes of acculturation to students and the theoretical and methodological bases of forming an acculturation worldview in them are researched. In this regard, foreign and national researches have been scientifically studied. Based on this goal, this article aims to study the issues of inculcating the sincerity of cultural relations in the educational process and forming acculturative skills in students. Based on this goal, it is appropriate to analyze the essence of the concept of acculturation, its definition in dictionaries, and to research the need to create socio-pedagogical mechanisms for the formation of acculturative skills.